THE KOMBINASI STRAIN COUNTERSTRAIN DAN INFRARED SAMA BAIK DENGAN KOMBINASI CONTRACT RELAX STRETCHING DAN INFRARED TERHADAP PENURUNAN NYERI MYOFASCIAL PAIN SYNDROME OTOT UPPER TRAPEZIUS PADA MAHASISWA FISIOTERAPI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Prianthara, I Made Dhita; Winaya, I Made Niko; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia, 2015)
Myofascial pain syndrome is a musculoskeletal disorder characterized by presence of trigger points in tautband of skeletal muscle. Myofascial pain syndrome causes decrease in daily activities such as difficulty in moving the neck. The objective of this study was to compare the combination of strain counterstrain and infrared with combination of contract relax stretching and infrared to reduce pain in the myofascial pain syndrome of trapezius muscle. This research was an experimental study with pre and post test control group design. Total sample is 22 subject were divided into two groups. The first group was given strain counterstrain and infrared intervention, while the second group was given contract relax stretching and infrared intervention. Pain was measured by VAS (visual analogue scale). This research was found that mean difference of VAS before and after intervention in each group were tested with paired sample t-test and the result obtained p = 0.000 with mean 2.309±0.996 for the first group and p = 0.000 with mean 2,118±0,855 for the second group. The result means that in each group were significantly decreased pain. From the Independent sample t-test obtained by the difference of first group with second group is p=0.635 where p>0.05. From these results it can be concluded that the combination of strain counterstrain and infrared showed no significant difference as combination of contract relax stretching and infrared to reduce pain in myofascial pain syndrome upper trapezius.
Keywords: Myofascial pain syndrome, strain counterstrain, contract relax stretching, infrared, VAS